PENGEMBANGAN GAWANG MINI DALAM MENINGKATKAN KOORDINASI MATA DAN KAKI TERHADAP KETEPATAN TENDANGAN JARAK JAUH ANAK TUNAGRAHITA SEDANG DI SLBN 1 MAKASSAR - Bustan, Shinta Damayanti; Bastiana, Bastiana; Usman, Usman (-, 2025)
This research examines the development of mini goal media to improve the ability of mentally retarded students in eye and foot coordination for the accuracy of long-range kicks at SLBN 1 Makassar. The formulation of the problems in this study are: (1) What is the level of need for developing mini goals to improve the ability to coordinate eyes and feet for the accuracy of long-range kicks for mentally retarded children at SLBN 1 Makassar? (2) How is the prototype for developing a mini goal to improve the ability to coordinate eyes and feet for the accuracy of long-range kicks for mentally retarded children at SLBN 1 Makassar? (3) What is the level of validity and practicality of using mini goals in the development of mini goals to improve eye and foot coordination for the accuracy of long-range kicks for mentally retarded children at SLBN 1 Makassar. The data collection instruments used were questionnaires and validation tests. The subjects in this study were 2 teachers at SLBN 1 Makassar and 2 validators. This research is research and development (R&D) using the 4-D model. The data obtained were analyzed using quantitative descriptive analysis. Analysis of the teacher's needs for the media is very necessary at the school, the prototype of the mini goal media has been made by modifying the previous media, has been validated by 2 validators and 2 teachers at SLBN 1 Makassar for practicality tests, and the results of the validity and practicality test for the development of mini goals feasible and can be used to improve eye and foot coordination for the accuracy of long-range kicks at SLBN 1 Makassar. The results of this study concluded that the results of the validity test for developing mini goal media were feasible and could be used to improve eye and foot coordination on the accuracy of long-range kicks for moderately mentally retarded students at SLBN 1 Makassar.